A Preliminary Investigation of Freeze Storage on the Production Trimethylamine Nitrogen in Leiognathus splendens (Family: Leiognathidae) - Senthil kumar, B (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The aim of the present study is evaluating the effectiveness of TMA-N as parameter estimating the freshness of fish and the impact of storing fish with gut and without gut in the production of TMA-N. The increase in the amount of TMA-N in the fresh fish was highly significant (p< 0.001) from 2.72 ± 0.194 to 4.244 ± 0.276 after 4 hours of refrigerated storage and to 8.584± 0.921 after 24 hours of storage in refrigeration. TMA-N values were significantly elevated in both with gut and without gut when compared to fresh fish.